FRI0122 EFFICACY AND PATIENT-REPORTED OUTCOME MEASURES FROM A TWO-PART MULTICENTER, PLACEBO-CONTROLLED, RANDOMIZED WITHDRAWAL TRIAL OF REPOSITORY CORTICOTROPIN INJECTION FOR PERSISTENTLY ACTIVE RHEUMATOID ARTHRITIS. (13th June 2020) - Fleischmann, R.; Furst, D.; Wan, G.; Panaccio, M.; Liu, J.; Zhu, J.; Brasington, R.
Abstract : Background: Repository corticotropin injection (RCI) is a naturally sourced complex mixture of adrenocorticotropic hormone analogs and other pituitary peptides approved for short-term adjunctive treatment of rheumatoid arthritis (RA). Objectives: This two-part, international, multicenter, placebo (PBO)-controlled study assessed the efficacy of RCI in persistently active RA patients (pts) using clinical and patient-reported outcome measures (PROMs) (ClinicalTrials.gov NCT02919761 ). Methods: Adults ≥18 years with persistently active RA (DAS28-ESR >3.2) despite disease-modifying anti-rheumatic drug and glucocorticoid use received open-label RCI (80 U) subcutaneously 2x/week (BIW) for 12 weeks (Part 1). Pts with DAS28-ESR <3.2 at Week (W) 12 entered the double-blind maintenance phase (Part 2) and were randomized to 80 U RCI or PBO BIW through W24. Efficacy endpoints included the proportion of pts who achieved DAS28-ESR <3.2 at W12 (primary) and maintained it through W24 (secondary). Mean changes from baseline (BL) were assessed for select PROMs (exploratory): Patient Global Assessment of Pain (PGAP); Patient Global Assessment of Disease Activity (PGADA); Health Assessment Questionnaire Disability Index (HAQ-DI); Functional Assessment of Chronic Illness Therapy – Fatigue (FACIT-F) scale; and Work Productivity and Activity Impairment (WPAI) questionnaire. Analyses used the modified intent-to-treat population (mITT-P; pts who received ≥1 dose of study drug and contributed any efficacy data). Results: In the mITT-P (N=259), 62.9% ( p <0.0001) achieved DAS28-ESR <3.2 at W12 (mean BL DAS28-ESR=6.3). In Part 2 (RCI, n=77; PBO, n=76), more RCI-treated pts maintained DAS28-ESR <3.2 at W24 (62.3%, p =0.035) vs. PBO (43.4%). Clinically significant improvements in PROMs from BL were observed through W12 and sustained to W24 (Table 1), with mean changes exceeding the reported minimal clinically important difference thresholds (MCIDs) for each. Conclusion: RCI for persistently active RA resulted in clinically significant improvements in efficacy endpoints and PROMs for up to 6 months in pts who continued and discontinued RCI after 3 months of initial therapy. References: Acknowledgments: Editorial support was provided by MedLogix Communications, LLC, Itasca, Illinois, under the direction of authors and funded by Mallinckrodt Pharmaceuticals. Disclosure of Interests: Roy Fleischmann Grant/research support from: AbbVie, Akros, Amgen, AstraZeneca, Bristol-Myers Squibb, Boehringer, IngelhCentrexion, Eli Lilly, EMD Serono, Genentech, Gilead, Janssen, Merck, Nektar, Novartis, Pfizer, Regeneron Pharmaceuticals, Inc., Roche, Samsung, Sandoz, Sanofi Genzyme, Selecta, Taiho, UCB, Consultant of: AbbVie, ACEA, Amgen, Bristol-Myers Squibb, Eli Lilly, Gilead, GlaxoSmithKline, Novartis, Pfizer, Sanofi Genzyme, UCB, Daniel Furst Grant/research support from: AbbVie, Actelion, Amgen, BMS, Corbus Pharmaceuticals, the National Institutes of Health, Novartis, Pfizer, and Roche/Genentech, Consultant of: AbbVie, Actelion, Amgen, BMS, Cytori Therapeutics, Corbus Pharmaceuticals, the National Institutes of Health, Novartis, Pfizer, and Roche/Genentech, Speakers bureau: CMC Connect (McCann Health Company), George Wan Employee of: Mallinckrodt Pharmaceuticals, Mary Panaccio Employee of: Mallinckrodt Pharmaceuticals, Jingyu Liu Employee of: Mallinckrodt Pharmaceuticals, Julie Zhu Employee of: Mallinckrodt Pharmaceuticals, Richard Brasington Speakers bureau: Amgen, Mallinckrodt Pharmaceuticals, Novartis, and Pfizer